Efektivitas Pemberian Kombinasi Teknik Relaksasi Nafas Dalam dan Aromaterapi Lavender terhadap Nyeri Post ORIF - Megani Ifa Algandira; Ahmad Ikhlasul Amal; Erna Melastuti; Dwi Retno Sulistyaningsih (STIKes Ibnu Sina Ajibarang, 2025)
Pain that is not promptly and properly managed can delay the recovery process. The combination of these two therapies is seen as necessary to maximize the patient's inhalation of aromatherapy and the use of appropriate techniques. This study uses a quasi-experimental design with a pretest-posttest control group design. The sample consisted of 36 respondents selected using purposive sampling and divided into an intervention group and a control group. The intervention group received a combination of deep breathing relaxation techniques and lavender aromatherapy, while the control group received only the deep breathing relaxation technique. Data were collected by measuring pain intensity using the Numerical Rating Scale (NRS) before and after the intervention. The results of this study show a significant reduction in pain levels in the intervention group compared to the control group (p<0.05). The combination of deep breathing relaxation techniques and lavender aromatherapy is proven to be effective as a non-pharmacological pain management intervention for post-ORIF pain.